Translation to Brazilian Portuguese, cultural adaptation and reproducibility of the questionnaire “Ankylosing Spondylitis: What do you know?” - Orlandi, Aline (2016)
CONTEXT AND OBJECTIVE: Ankylosing spondylitis (AS) generates inflammation and pain in entheses, peripheral joints and the spine. Education regarding AS can improve patients’ disability. Thus, it is important to assess patients’ knowledge. There is no instrument in the literature for assessing knowledge of AS in Portuguese. The aim here was to translate to the Brazilian Portuguese language, culturally adapt and test the reliability of the questionnaire “Ankylosing Spondylitis: What do you know?” and to correlate the findings with other factors. DESIGN AND SETTING: Original article regarding validation of questionnaire, produced at the Federal University of Sao Paulo (Unifesp). METHODS: For translation and cultural adaptation, Guilleman methodology was used. After the first phase, the reliability was tested on 30 patients. Correlations between these scores and other factors were examined. RESULTS: In the interobserver assessment, the Pearson correlation coefficient and Cronbach’s alpha were 0.831 and 0.895, respectively. In the intraobserver evaluation, the intraclass correlation coefficient and Cronbach’s alpha were 0.79 and 0.883, respectively. At this stage, the score for area of knowledge A showed correlations with ethnicity and education; the score for area D, with age; the total score and scores for areas A and B with “social aspects” of SF-36; and the score for area D with “pain”, “vitality” and “emotional aspects” of SF-36. CONCLUSION: The Brazilian version of the questionnaire “Ankylosing Spondylitis: What do you know?” was created. It is reproducible and correlates with education level, ethnicity and the SF-36 domains “social aspects” and “emotional aspects”